Development of a screening workflow to identify patient needs in an interdisciplinary oncological day clinic Entwicklung eines Screening-Workflows zur Erkennung von Patientenbedürfnissen in einer interdisziplinären onkologischen Tagesklinik - Windschuttl, Sandra; Pukrop, Tobias; Herrmann, Anne; Lindberg-Scharf, Patricia; Heudobler, Daniel; Herr, Wolfgang; Andreesen, Reinhard; Klinkhammer-Schalke, Monika; Koller, Michael (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Introduction: The diagnosis of cancer leads to high levels of emotional distress in many patients. Quality of life is an important therapeutic goal in this context. A quality-of-life guide was implemented in the oncological day clinic (ICT) at the University Hospital of Regensburg (UKR) in order to individually support outpatients, help them with their questions and needs and improve their quality of life. Methods: A screening tool is necessary for the structured assessment of quality of life/needs in the routine of tumor therapy and follow-up. As part of a mixed-methods study, focus groups with health professionals/patients were organized to specify the needs of cancer patients. On this basis, the literature was searched for questionnaires covering these needs in order to adapt an ICT-specific questionnaire and integrate it with the help of a workflow. Results: A total of 333 individual aspects were brought up by the participants in focus groups on the needs of cancer patients in various phases of treatment/with various tumor entities. Since none of the questionnaires identified in the literature met our requirements, a new screening tool containing elements from different standardized forms and the results of the focus groups was developed and a new workflow created to integrate the questionnaire into the ICT routine. Discussion: By interviewing health experts from different areas and patients with different tumor entities, the needs of cancer patients over different stages of the disease and additional possible differences between the cancer entities were identified and recorded. Through the implementation of a quality-of-life guide in the ICT, a structured assessment of the quality of life and an analysis of patient needs can take place with the help of the screening. A workflow was created to integrate screening into routine care. In addition, the questionnaire was designed in such a way that it can be used repeatedly at various points in time. In order to cover important stages in the course of therapy and to determine how patient needs change over the course, patients should be asked to complete the questionnaire several times after specified time intervals. Conclusion: The questionnaire is intended to assess the needs of cancer patients receiving outpatient treatment in a structured manner. Now it needs to be explored how the new screening tool and workflow interact and perform in clinical practice and how they help to improve patients’ quality of life. It is also interesting to analyze which patients accept the advice offered by the quality-of-life guide and which needs are expressed most frequently.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Outpatient tumor therapy; Patient needs; Psycho-oncological care; Quality of life; Screening